2017
DOI: 10.1016/j.landusepol.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Controlling deforestation in the Brazilian Amazon: Regional economic impacts and land-use change

Abstract: Brazil confirmed targets for reducing greenhouse gas emissions in 2008, including an 80% reduction in deforestation in the Amazon by 2020. With this in mind, we investigated the trade-off between environmental conservation and economic growth in the Amazon. The aim of this study is to project the economic losses and land-use changes resulting from a policy to control deforestation and the rise in land productivity that is necessary to offset those losses. We developed a Dynamic Interregional Computable General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 15 publications
0
24
0
6
Order By: Relevance
“…8 For a complete description of equations and solution method, see Dixon and Rimmer (2002) and Wittwer (2012). 9 See Carvalho et al (2017) and Ribeiro et al, (2018) for more information about the regionalization procedure. 10 With the exception of the regional population growth variable, the baseline scenario does not incorporate other regional characteristics; accordingly, regions follow national macroeconomic trends.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 For a complete description of equations and solution method, see Dixon and Rimmer (2002) and Wittwer (2012). 9 See Carvalho et al (2017) and Ribeiro et al, (2018) for more information about the regionalization procedure. 10 With the exception of the regional population growth variable, the baseline scenario does not incorporate other regional characteristics; accordingly, regions follow national macroeconomic trends.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology ensures the consistency of the database with the official information available for the country. Carvalho, Domingues, and Horridge () and Ribeiro et al () apply this procedure to regionalize the official database in the analysis of the Amazon micro regions—rest of Brazil and the Northeast micro regions—rest of Brazil, respectively. Our model accounts for the 27 Brazilian federative units, contemplating all of the nine states in the Brazilian Northeast, as well as the trade flows among them and the rest of the states in Brazil.…”
Section: Cge Model and Databasementioning
confidence: 99%
See 1 more Smart Citation
“…The Ministry of Science and Technology estimated average cost per hectare of US $3000 and abatement cost of US $ 9.22 per tonne of CO 2 e avoided. It was found that to achieve the mitigation potential of 414 MtCO 2e between 2012 and 2050, it would be necessary to invest US $3.8 billion to restore an additional 4.1 million hectares to the benchmark scenario used in the report …”
Section: Discussion – Ndc Land Use and Emissionsmentioning
confidence: 99%
“…The empirical basis of CGE models is the interregional social accounting matrix (SAM), which records the revenues and expenses of all agents in the economy, classified as businesses, factors of production, households, government and the rest of the world (or the country), and provides the input-output coefficients of an economy. 16 In this study, two main data sources feed the CGE model with balanced input-output coefficients: the interregional SAM for the baseline year of 2009, 17 which describes the current sectors of the economy, and economic modeling of the biobased processes. The macroeconomic CGE model was used in combination with a spreadsheet tool containing the calculated GHG emission factors and primary energy supply factors for each sector in the economy and each biobased product analyzed.…”
Section: Methodology Cge Modelmentioning
confidence: 99%